AKIBAT HUKUM PERNIKAHAN SIRI TERHADAP HAK WARIS ANAK BERDASARKAN PUTUSAN MK NO. 46/PUU-VIII/2010 - Lukmawati, Endah; Syamsuddin, Syamsuddin; Baehaqi, Baehaqi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
Marriage Inheritance Rights is something sacred for someone, but sometimes on the way many people have married want to remarry and of course this marriage is a marriage that is not registered or under marriage the hand that is harmed is the woman's side. According to marriage law no. 1 of 1974, Children born outside marriage only have civil relations with their mother and mother's family only. However, with the case of Machica Mohtar in 2010, a judicial review of Law No. 1 of 1974 is necessary so that children resulting from marriage under a marriage can claim their rights or receive protection and inheritance rights from their biological father. The formulation of the problem in this study is the Consequences of Siri Marriage Law on Child Inheritance Rights Based on Court Decree No. 46/PUU-VIII/2010In this study, normative legal research was chosen as the type of research. Normative research is a type of research that uses information from library research books. The result of this research is the issuance of MK Decision No. 46/PUUVII/2010, the background is the existence of legal uncertainty related to Article 2 paragraph 2 and 43 paragraph 1 of the Marriage Law, related to legal marriage and children born out of wedlock only have civil relations with the mother and her family, namely: 1. Open to become the heir of the father of siri marriage, 2. Has the right to receive a distribution of inheritance from the inheritance of his parents who are siri. 3. Has the right to inherit from his father.